2017
DOI: 10.1108/imr-12-2015-0292
|View full text |Cite
|
Sign up to set email alerts
|

Standardization versus adaptation of global marketing strategies in emerging market cross-border acquisitions

Abstract: ). AbstractPurpose: The recent increase in the presence of emerging-market firms (EMFs) in global markets requires a closer examination of their international marketing strategies (including branding). This paper examines the factors behind the standardization or adaptation of global marketing strategies adopted by EMFs for their cross-border acquisitions.Methodology/Approach: This paper examines the determinants of the marketing strategies adopted by Indian and Chinese firms for their cross-border acquisition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 91 publications
1
53
0
Order By: Relevance
“…The position of Haier in Figure as a relative globalized (with central decision making) is in line with Rao‐Nicholson and Khan (), who found that when Chinese state‐owned and private‐owned companies make cross‐border mergers and acquisitions, they are more likely to standardize their marketing strategies toward target foreign companies, as these Chinese MNCs are often restricted from exercising the full breadth of their strategic decision making because of political restrictions. In this way, the standardization strategy also facilitates the Chinese companies' easier implementation of their home governments' policies.…”
Section: Case Findings—electroluxsupporting
confidence: 78%
See 1 more Smart Citation
“…The position of Haier in Figure as a relative globalized (with central decision making) is in line with Rao‐Nicholson and Khan (), who found that when Chinese state‐owned and private‐owned companies make cross‐border mergers and acquisitions, they are more likely to standardize their marketing strategies toward target foreign companies, as these Chinese MNCs are often restricted from exercising the full breadth of their strategic decision making because of political restrictions. In this way, the standardization strategy also facilitates the Chinese companies' easier implementation of their home governments' policies.…”
Section: Case Findings—electroluxsupporting
confidence: 78%
“…Considering that more emerging‐market firms (EMFs) are entering the global market for white goods (e.g., Haier from China), it is interesting to consider the importance of country cultural background and institutional factors of these state‐owned and private‐owned MNCs. Rao‐Nicholson and Khan () found that especially the institutional factors are very important in explaining these MNCs' degree of standardization (centralization) in the global strategy.…”
Section: Literature Review/research Questionsmentioning
confidence: 99%
“…One recent study investigated the standardization or adaptation of target brand in cross-border acquisitions by Indian and Chinese firms and found out institutional factors have a strong effect on organizational brand identity (Rao-Nicholson & Khan, 2017). This study extends the field of research on adaptation versus standardization of global marketing strategies (Vrontis, Thrassou, & Lamprianou, 2009) adopted in the cross-border M&As from developed countries to emerging economies.…”
Section: Introductionmentioning
confidence: 54%
“…As Balmer and Dinnie (1999) point out, M&As underperforming may be explained by how corporate brands (and images) are not given adequate attention. Despite the importance of brand management (Hogan, Glynn, & Bell, 2006;Kumar & Blomqvist, 2004;Srivastava, 2012), there has been scant attention to brand management in M&A literature (Bauer, Matzler, & Wille, 2012;Rao-Nicholson & Khan, 2017;Vu, Shi, & Hanby, 2009). Scholars acknowledge the importance of post-acquisition integration in M&A (Graebner, Heimeriks, Huy, & Vaara, 2016), such as the human factors in M&A (Cartwright & Cooper, 1993;Larsson & Finkelstein, 1999), the influences of sociocultural factors (Sarala, Junni, Cooper, & Tarba, 2016), the role of customers (Öberg, 2014), negotiation process (Ahammad, Tarba, Liu, Glaister, & Cooper, 2016) and knowledge transfer , among others, while brands, that constitute important values when deciding the price of a target (Murphy, 1990), thus is only discussed to a limited extent (Basu, 2006;D.…”
Section: Introductionmentioning
confidence: 99%
“…The merger and acquisition (M&A) literature has remained scarce on descriptions about marketing integration (Christofi, et al, 2017;Homburg and Bucerius, 2005;Öberg, 2013;Öberg and Tarba, 2013;Zollo and Meier, 2008). Those attempts to approach the topic (Anderson et al, 2001;Balmer and Dinnie, 1999;Capron and Hulland, 1999;Rao-Nicholson and Khan, 2017) have focused on 1 brand equity and integration 2 marketing integration related to consumer goods 3 customer reactions in business-to-business (B2B) settings.…”
Section: Introductionmentioning
confidence: 99%